Aqueous Self‐Assembly of Y‐Shaped Amphiphilic Block Copolymers into Giant Vesicles. Issue 6 (6th February 2017) - Li, Hanping; Jin, Yong; Fan, Baozhu; Lai, Shuangquan; Sun, Xiaopeng; Qi, Rui
Abstract : A series of newly Y‐shaped amphiphilic block polyurethane copolymers with two hydrophilic poly(ethylene oxide) (PEO) tails and one hydrophobic alkyl tail is synthesized, which can self‐assemble into spherical micelles, small vesicles, and giant unilamellar vesicles by increasing the copolymer concentrations with a direct dissolution method in aqueous solution. Abstract : The preparation and aqueous self‐assembly of newly Y‐shaped amphiphilic block polyurethane (PUG) copolymers are reported here. These amphiphilic copolymers, designed to have two hydrophilic poly(ethylene oxide) (PEO) tails and one hydrophobic alkyl tail via a two‐step coupling reaction, can self‐assemble into giant unilamellar vesicles (GUVs) (diameter ≥ 1000 nm) with a direct dissolution method in aqueous solution, depending on their Y‐shaped structures and initial concentrations. More interesting, the copolymers can self‐assemble into various distinct nano‐/microstructures, such as spherical micelles, small vesicles, and GUVs, with the increase of their concentrations. The traditional preparation methods of GUVs generally need conventional amphiphilic molecules and additional complicated conditions, such as alternating electrical field, buffer solution, or organic solvent. Therefore, the self‐assembly of Y‐shaped PUGs with a direct dissolution method in aqueous solution demonstrated in this study supplies a new clue to fabricate GUVs based on the geometric design of amphiphilic polymers.